Caring for the caregiver: Why policy must shift from addressing needs to enabling caregivers to flourish - Beach, Brian; Bélanger-Hardy, Louise; Harding, Susana; Rodrigues Perracini, Monica; Garcia, Linda; Tripathi, Ishika; Gillis, Margaret; Dow, Briony (Frontiers in Public Health, 2022)
Policies supporting caregivers (“caregiver policies”) are limited in the extent to which they meet the needs of those who care for others. Where policies do exist, they focus on relieving the burdens associated with caring or the needs of the person they care for, rather than consider the holistic needs of the caregiver that would enable them to flourish. We argue that the established approach to caregiver policies reflects a policy failure, requiring a reassessment of current practice related to caregiver support. Often, caregiver policies target the care recipient rather than the caregiver’s needs. Through a consultative exercise, we identified five areas of need that existing caregiver policies touch upon. Yet current approaches remain piecemeal and inadequate in a global context. Caregiver policies should not just relieve burden to the extent that caregivers can continue in the role, but they should support caregivers to flourish, and future work may benefit from drawing on related frameworks from positive psychology, such as the PERMA™ model; this is important for both policymakers and researchers.